Identifikasi Ordo Odonata di Kampus II Universitas Islam Negeri Sumatera Utara - Hartono, Adi; Fahira, Nanda; Dalimunthe, Rizka Ramadhani; Munthe, Dea Wahdania; Ayundari, Sella (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
Odonata is one of the orders of insects that has an important role as an indicator of the quality of aquatic ecosystems as well as a component in the food chain. The diversity of Odonata species in urban areas, including campus environments, is often not optimally documented, even though this information is crucial as a basis for environmental management and conservation of local species. Campus II of the State Islamic University of North Sumatra, which has a small aquatic ecosystem, such as ponds and riparian vegetation, is a potential habitat for the existence of the Odonata order. However, until now there has been no scientific study documenting the species in the area. Therefore, this study was conducted with the aim of identifying Odonata species found in the Campus II environment of the State Islamic University of North Sumatra. This research is an exploratory research with data collection techniques using direct sampling methods in the field. Specimen collection was carried out using insect nets, visually documented through digital cameras, and identified using taxonomic determination keys as the main reference. Stationery is used for recording data during field observation. The data from the research were analyzed qualitatively using the Miles and Huberman model analysis technique which involved four systematic steps, namely data collection, data reduction, data presentation, and conclusion drawn. The results of the study showed that in the Campus II area of the State Islamic University of North Sumatra, two species of Odonata were found, namely Diplacodes trivialis from the suborder Anisoptera and Agriocnemis pygmaea from the suborder Zygoptera. These two species show adaptation to artificial aquatic habitats in the campus environment. This study concluded that even though the area is semiurban, there is still a diversity of Odonata species that needs attention. The implications of this study are expected to be an initial reference for the development of local insect biodiversity studies as well as the basis for the formulation of insect-friendly habitat management policies in university areas.